Organic deposition presents challenges in Brazil's offshore fields - Marques, L. C C; Machado, A. L C; Garcia, R. L P; Soldan, A. L.; Campagnolo, E. A. [UNESP] (My University, 1997)
Over the last quarter century, Petrobras has continually developed tools, techniques and methods to predict and to deal with organic deposition problems in offshore fields.